Law Enforcement in Building Community Trust to Positive Legal Quality - Ni Putu Sawitri Nandari (Sociological Jurisprudence Journal, 2018)
Law enforcement is done to restore the balance between the rights and obligations of the people, in realizing order and security for the members of the community.In a state of law, the rule of law must be manifestly realized, so that when there is a violation of law then the law must be enforced. The decline in the authority of the law is not solely due to the weakness of law enforcement, but there are many factors that cause the dissolution of public confidence in the existence of positive law in Indonesia, among others from the aspects of society itself, legal aspects, both material law and formal law and law enforcement aspects. Law enforcers must be able to portray their respective roles in upholding the law, justice and truth according to the sense of community justice. Through this enforcement, the law is actually implemented so that it can add the image and legal authority and can build public trust on the quality of positive law of Indonesia.